2012
DOI: 10.1007/s10597-012-9542-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depressive Symptoms and Related Factors in Japanese Employees as Measured by the Center for Epidemiologic Studies Depression Scale (CES-D)

Abstract: This study aimed to examine the prevalence of depressive symptoms and related factors in Japan. For this purpose, a questionnaire including the Center for Epidemiologic Studies Depression Scale (CES-D) was administered to employees from Akita prefecture, Japan. The cutoff point for CES-D scores was 16 or above (high scorers). We analyzed the results of this survey in order to identify relationships between the prevalence of high scores on the CES-D, sociodemographic status, and employment-related variables. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 24 publications
6
31
2
Order By: Relevance
“…Compared to older participants, young and middle-aged participants were at greater risk of depressive symptoms. This finding is consistent with a previous study conducted on Japanese employees in companies [36]. Based on this evidence, attention to this age population is needed to prevent mental health problems.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Compared to older participants, young and middle-aged participants were at greater risk of depressive symptoms. This finding is consistent with a previous study conducted on Japanese employees in companies [36]. Based on this evidence, attention to this age population is needed to prevent mental health problems.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the prevalence rates of depressive symptoms based on CES-D scores of 16 points or more were 17.3% in males and 31.7% in females. While few studies have been conducted on farmers in Japan, the prevalence in males seemed to be relatively lower than those cited in previous evidence, using the CES-D with the same cut off point for workers and middle-aged adults in Japan, which range from 23% to 48% [35][36][37]. Our results also indicated that males had a lower prevalence of depressive symptoms than females, which was consistent with other previous studies [21,38,39].…”
Section: Discussionsupporting
confidence: 89%
“…The scale consists of 20 items with 4 options that describe the frequency of respondents' feelings in the past week ranging from 0 “rarely or none of the time (less than 1 day)” to 3 “most or all of the time (5 to 7 days).” The severity of depressive symptoms increases with a higher summed score that ranges from 0 to 60. To estimate the prevalence of depressive symptoms, a CES-D score of ≥16 was defined as “depressive symptoms” in this study [4, 6, 31]. The CES-D scale has demonstrated good reliability and validity in the Chinese occupational population [6, 31].…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of depression in the working population of some countries seems to vary between 5 % and 10 % (13-16). Possible risk factors for the development of depression in the working population include female gender, alcohol consumption, high psychological demands of a job, psychosocial work stressors, job insecurity, and drug abuse (17).…”
mentioning
confidence: 99%